Neurology consults in emergency departments: Opportunities to streamline care. Issue 2 (April 2020) - Zhao, Cindy; Lee, Kathleen; Do, David
Abstract : Objective: To use the variations in neurology consultations requested by emergency department (ED) physicians to identify opportunities to implement multidisciplinary interventions in an effort to reduce ED overcrowding. Methods: We retrospectively analyzed ED visits across 3 urban hospitals to determine the top 10 most common chief complaints leading to neurology consultation. For each complaint, we evaluated the likelihood of consultation, admission rate, admitting services, and provider-to-provider variability of consultation. Results: Of 145, 331 ED encounters analyzed, 3, 087 (2.2%) involved a neurology consult, most commonly with chief complaints of acute-onset neurologic deficit, subacute neurologic deficit, or altered mental status. ED providers varied most in their consultation for acute-onset neurologic deficit, dizziness, and headache. Neurology consultation was associated with a 2.3-hour-longer length of stay (LOS) (95% CI: 1.6–3.1). Headache in particular has an average of 6.7-hour-longer ED LOS associated with consultation, followed by weakness or extremity weakness (4.4 hours) and numbness (4.1 hours). The largest estimated cumulative difference (number of patients with the specific consultation multiplied by estimated difference in LOS) belongs to headache, altered mental status, and seizures. Conclusion: A systematic approach to identify variability in neurology consultation utilization and its effect on ED LOS helps pinpoint the conditions most likely to benefit from protocolized pathways.